Peningkatan Pengetahuan Komunitas Lansia Dalam Mencegah Dan Mengatasi Nyeri Punggung Bawah Berbasis Home Program Di Kelurahan Bandungrejosari Kota Malang - Ananda Iftina Nida’ Wafia; Dimas Sondang Irawan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Lower back or waist pain is a disorder in musculoskeletal position due to incorrect ergonomics, characterized by pain in the muscle area between the costal border and the inferior gluteal fold. Risk factors that can influence the incidence of lower back pain are age, gender, body mass index, smoking habits, lack of exercise, years of work, work position, and heavy workload. This community service is a forum to improve and provide education to the elderly about prevention and how to deal with lower back pain using a home program. This service activity was carried out using the counseling method with approximately 20 respondents participating. After being given a presentation of material regarding low back pain and a demonstration regarding recommended home exercises/home programs, most respondents understood and were able to explain the definition, risk factors, symptoms and prevention of low back pain.